Barca innovation Hub
The ist the the center for sports knowledge and innovation of the FC Barcelona. They there produce and share knowledge, codevelop, test, and launch new products and services and promote and nurture an ecosystem. Fokus: The goal is to create an ecosystem that bolsters knowledge and innovation. This ecosystem is based on a model that promotes a culture of excellence and collaboration with prestige brands, universities, research centers, startups, entrepreneurs, students, athletes, investors and visionaries from all over the world.